A combined maximum-likelihood analysis of the high-energy astrophysical neutrino flux measured with IceCube - Aartsen, M. G.; Abraham, K.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Golup, Geraldina Tamara; Wallraff, M.; Wandkowsky, N.; Weaver, Ch.; Wendt, C.; Westerhoff, S.; Whelan, B. J.; et al. (IOP Publishing, 2015)
Fil: Aartsen, M. G.. University of Adelaide; Australia